A stochastic model on the mean time to recruitment for a two graded manpower system associated with a univariate policy of recruitment involving combined thresholds using same geometric process for inter-decesion times - Srinivasan, A; Vasudevan, V (Recent Research in Science and Technology, 2013)
In this paper, an organization with two grades subjected to loss of manpower due to the policy decisions taken by the organization is considered. A mathematical model is constructed and an appropriate univariate recruitment policy, based on shock model approach involving combined optional thresholds and combined mandatory thresholds for the loss of manpower in the organization is suggested. The expected time for recruitment is obtained for different cases on the distribution of the thresholds when (i) the loss of manpower forms a sequence of independent and identically distributed exponential random variables and (ii) the inter-decision times for the two grades form the same geometric process. The analytical results are substantiated by numerical illustrations and relevant conclusions are presented.